Act of defiance [large type] - Andrews, Brian, 1973-; Wilson, Jeffrey, 1963-; Clancy, Tom, 1947-2013 (Clancy, Tom, 1947-2013. Jack Ryan novel, 2024)
"U.S. intelligence says there's something going on in Russia. While their land forces have been decimated by corruption and incompetence, the Navy seems to be puring money into some secret project. Analysts are stumped, until the know is untangled by one bright young woman at the Office of Naval Intelligence--Katie Ryan, the youngest daughter of President Jack Ryan. Like her father, she sees patterns where other don't, and she's determined that the Russians are about to launch a super missile submarine, the Belgorod. Now the race is on to determine where the sub is and whether it poses a threat to the continental United States"--